INTERNALISASI PENDIDIKAN MULTIKULTURAL DI PESANTREN - Khoiriyah Khoiriyah (Tarbiyatuna Kajian Pendidikan Islam, 2023)
Multiculturalism education has been widely studied with different scientific perspectives. Islamic boarding schools as educational organizations have an alternative side in completing their learning cycle, which lies in the framework that is implemented, including perceiving diversity (pluralism, respecting equality/balance, creating resilience, and respecting human qualities. This multicultural learning is basically a learning system designed to create an informed and educated society, not the general public which avoids existing cultural and son''social factors. The model applied by Islamic boarding schools in multicultural learning among students is very varied. Multicultural education in Islamic boarding schools varies greatly. The kiai's insights and ideas regarding Islam that is inclusive, tolerant, moderate, and harmonious bring pesantren and their students to obtain Islam that is friendly and rahmatan lil'alamin, not an Islam that is rigid and radical towards adherents of other religions and also towards developing cultures. around the boarding school. Multicultural teaching is not explicitly given as a specific subject or study, but through various opportunities and training in Islamic boarding schools